1997
DOI: 10.1099/00207713-47-3-883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rickettsiae Isolated in Japan as Coxiella burnetii by 16S rRNA Sequencing

Abstract: The 16s rFWA genes of Japanese Coxiella isolates obtained from various sources and geographical areas were directly sequenced by dideoxynucleotide chain termination methods in which Taq DNA polymerase was used. The levels of sequence similarity among Japanese, European, and American isolates were more than 99%, and the Japanese isolates were identified as Coxiella burnetii. C. burnetii strains isolated worldwide, including Japan, were found to be very similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Samples with positive PCR products (confirmed through Sanger sequencing) were subjected to another Coxiella genus-specific PCR targeting 1.45 kb of the 16S rRNA gene (long 16S) using the primer pairs Cox-16s-1457F (QR-F0 5"ATTGAAGAGTTTGATTCTGG) and Cox-16s-1457R (QR-R0 5" CGGCTTCCCGAAGGTTAG) (Masuzawa et al, 1997). All PCRs contained 2 μL of DNA extracted from ticks, 1 x PCR buffer, 2.5 mM MgCl 2 , 1 mM dNTPs, 0.01 mg BSA (Fisher Biotech, Australia), 1.25 U Perfect Taq Polymerase (5 Prime, Germany), and 400 nM of each primer in a total volume of 25 μL.…”
Section: Conventional Pcrmentioning
confidence: 99%
“…Samples with positive PCR products (confirmed through Sanger sequencing) were subjected to another Coxiella genus-specific PCR targeting 1.45 kb of the 16S rRNA gene (long 16S) using the primer pairs Cox-16s-1457F (QR-F0 5"ATTGAAGAGTTTGATTCTGG) and Cox-16s-1457R (QR-R0 5" CGGCTTCCCGAAGGTTAG) (Masuzawa et al, 1997). All PCRs contained 2 μL of DNA extracted from ticks, 1 x PCR buffer, 2.5 mM MgCl 2 , 1 mM dNTPs, 0.01 mg BSA (Fisher Biotech, Australia), 1.25 U Perfect Taq Polymerase (5 Prime, Germany), and 400 nM of each primer in a total volume of 25 μL.…”
Section: Conventional Pcrmentioning
confidence: 99%
“…Occasionally, a 33 to 42 kb plasmid (depending on the plasmid considered) can be observed but its function remains to be determined [33]. Bacterial isolates can be identified by a probe to 16S ribosomal RNA (rRNA), which is highly conserved [34]. Genetic heterogeneity of Coxiella burnetii is limited with approximately 30 distinct variants [35].…”
Section: Causal Agentmentioning
confidence: 99%
“…Masuzawa et al [42] showed that the levels of sequence similarity of 16S rRNA genes among Japanese isolates (including 1M, 27M, 50F, 58T and 605) and American isolates (Bangui, Ohio and G Q212) were higher than 99%.…”
Section: Banding and Immunoblotting Patterns Of Proteins And Lipopolymentioning
confidence: 99%